Expanding and mainstreaming sociohydrology toward transdisciplinary praxis - Nakamura, Shinichiro; Kreibich, Heidi; Haeffner, Melissa; Mukherjee, Jenia; Di Baldassarre, Giuliano; Sakamoto, Maiko; Sugiura, Mikiko; Blöschl, Günter; Oki, Taikan; Sivapalan, Murugesu (Frontiers in Water, 2025)
Since its development in the early 2010s, sociohydrology has deepened our understanding of the long-term coevolution of humans and water by integrating insights from both the natural and social sciences, while also fostering an interdisciplinary community. Its modus operandi to date has been to focus on emergent phenomena, manifesting as unintended consequences, in a variety of contexts. The compound disaster that struck Japan’s Noto Peninsula in 2024, and similar experiences in other parts of the world, underscore the urgent need for systemic approaches that are co-developed by academia and practitioners and focus on context-specific solutions. This perspective piece thus calls for expanding and mainstreaming sociohydrology toward transdisciplinary praxis—transforming it into a dynamic and solution-oriented field that is more inclusive at all levels. Sociohydrology must become a driving force for innovation—promoting sustainable solutions that engage and empower local actors through transformative-transdisciplinary actions—involving real people in real places. Only through such transformative praxis can we co-create equitable, sustainable, and context-sensitive responses to the world’s most pressing water challenges.